(untitled) (Sains Humanika, 2009)
This paper investigates the role of attitude and attributes of excellent Islamic Education teacher’s in enhancing the effectiveness of the teaching and learning process of the subject in secondary schools. The investigation was carried out in eight secondary schools throughout Malaysia. A set of questionnaires was distributed among secondary schoool students to evaluate the attitude of the excellent Islamic Education teachers in the classroom. Data was then analysed using SPSS version 16.0. It was found that the total mean of students’ perception on the attitude of the teachers and their motivation was at high level: i.e the mean attitude of teachers personality (mean = 4.50), attitude toward students (mean = 4.00), and student’s motivation (mean = 4.30). In addition, teachers’ attitude has an apparent relationship with student’s motivation during their teaching and learning process in the classroom.